Postpartum as the Dominant Period of Maternal Death in Indonesia: Analysis of Survey Results - Lisa Suarni; Warjidin Aliyanto; R. Pranajaya; Sono Sono (Poltekkes Kemenkes Tanjung Karang, 2026)
Maternal mortality remains a critical public health challenge in Lampung Province, which consistently records one of the highest maternal mortality rates in Sumatra and has not yet reached the national Sustainable Development Goals (SDGs) target. Understanding the temporal patterns and dominant risk factors of maternal deaths is essential for designing more targeted preventive strategies. This case-control study included 193 respondents: 64 cases (maternal deaths) and 129 controls (surviving mothers), selected through purposive sampling from health facilities across Lampung Province. Data were obtained from medical records, maternal death audit reports, and structured interviews, then analyzed using univariate, bivariate (chi-square), and multivariate (binary logistic regression) approaches. The majority of maternal deaths occurred in the postpartum period (78.3%), with the highest concentration within the first 24 hours (63.1%), indicating this as the most critical vulnerability window in Lampung. Hemorrhage was the leading cause of death (53.9%), with most fatalities occurring within hospital settings (71.2%), suggesting that referral delays and suboptimal emergency obstetric care remain persistent challenges in the province. Binary logistic regression revealed that chronic diseases were the most dominant risk factor (OR = 3.80; 95% CI: 1.56–9.24), followed by irregular Antenatal Care visits (OR = 3.77; 95% CI: 1.58–8.99) and history of pregnancy complications (OR = 3.48; 95% CI: 1.45–8.34). Gestational age showed no significant association (p = 0.635). Urgent need for Lampung Province to strengthen early detection of chronic diseases through integrated ANC programs at the primary care level (Community Health Centers), improve emergency obstetric care quality, and reduce referral delays across districts to prevent avoidable maternal deaths.